Youth Language in Bangladesh - Awal, Abdul (My University, 2025)
This study explores the dynamic and evolving nature of the youth language in Bangladesh, examining both the linguistic features and the perceptions of young people about their language usage. Using a mixed-method approach, the research combines qualitative analysis of linguistic innovations with quantitative data gathered through surveys. The findings reveal significant changes in language practices among Bangladeshi youth, including the adoption of new slang, the mixing of codes with English and Hindi, and the creation of unique expressions that reflect modern values and technological influences. The study also highlights the positive perceptions of youth language in enriching cultural diversity and fostering effective communication among peers, while noting resistance to its acceptance in formal settings. The implications underscore the importance of understanding youth language as a significant cultural phenomenon with sociolinguistic impacts on identity, communication, and language evolution in Bangladesh.

Acest studiu explorează natura dinamică și în continuă evoluție a limbajului utilizat de tineri în Bangladesh, examinând atât trăsăturile lingvistice, cât și percepțiile tinerilor asupra modului în care folosesc limba. Folosind o abordare mixtă, cercetarea combină analiza calitativă a inovațiilor lingvistice cu date cantitative obținute prin sondaje. Rezultatele relevă schimbări semnificative în practicile lingvistice ale tinerilor din Bangladesh, inclusiv adoptarea unui nou jargon, amestecul de coduri lingvistice cu engleza și hindi, precum și crearea unor expresii unice care reflectă valorile moderne și influențele tehnologice. Studiul subliniază, de asemenea, percepțiile pozitive ale limbajului tinerilor în ceea ce privește îmbogățirea diversității culturale și facilitarea comunicării eficiente între colegi, remarcând totodată rezistența față de acceptarea acestuia în contexte formale. Implicațiile subliniază importanța înțelegerii limbajului tinerilor ca fenomen cultural semnificativ, cu impact sociolingvistic asupra identității, comunicării și evoluției limbii în Bangladesh.
Limba tinerilor din Bangladesh
Keywords: youth language; Bangladesh; linguistic innovation; code-mixing; youth perceptions; sociolinguistics; language evolution; limbajul tinerilor; inovație lingvistică; amestec de coduri; percepții ale tinerilor; sociolingvistică; evoluția limbii